The Impact of Educational Attainment on Employment Opportunities and Wages in Jordan - Hailat, Ahmad; Hailat, Mahmoud (Jordan Journal of Economic Sciences, 2021)
This paper investigates the impact of individual's educational attainment on employment opportunities and wages in Jordan using Jordan labor market Panel Survey 2010 and 2016 micro-data. Probit Models and Standard Linear regression Models are employed, and the main findings are follows. Educational attainment positively impacts employment and wages; as the educational level of an individual increases, so does his/her employment probability and the monthly wage. Effects of educational attainment on employment and wages are deteriorated in 2016 relative to 2010, however the effect remains positive and statistically significant. Employment and wages are positively associated with work experience and household wealth, and vary by gender. Finally, while wages vary across sectors, there is no significant evidence on wage disparities by nationality.